Identification of Appropriate Biodiversity Indicators for Ecologically Sustainable Forest Management at National Level - Tolunay, Ahmet; Akyol, Ayhan (Universiti Kebangsaan Malaysia, 2015)
Sustainable forest management (SFM) practices have started in 1999 in Turkey. A set of criteria and indicators, composed by the General Directorate of Forestry (GDF) on the basis of the criteria and indicators defined in the Pan-European and Near Eastern Processes, was enquired via a survey to serve this purpose. GDF tested the sustainability under the following titles: Situation of forest resources, biodiversity, health and vitality, production capacity and functions, protective functions and environmental and socio-economic functions. There were problems in identification and definition of SFM criteria and indicators. Biological diversity indicators has been selected, described and developed in this study. At this phase, the survey was completed upon receiving the views of the scientists interested in different dimensions of this topic as well as the views of other interest groups affiliated with forestry. As a result, there were 13 indicators that may be used as the basis of a regional or forest management unit level for the purpose of protecting, developing and maintaining biodiversity. Furthermore, these indicators are instruments, which may easily be used by relevant decision-makers in the management of forest resources in a more effective and productive manner.